TIME-BASED COMPETITION IN THE SUPPLY-CHAIN: THE ROLE OF THE LOGISTICS SERVICE PROVIDERS - Judit OLÁH; József POPP; Gabriella ANTAL (SEA: Practical Application of Science, 2018)

(untitled)
Among the service industries, the analysis logistics as an academic field which has a great influence on firms’ creation of value and competitiveness, and within this the analysis of firms providing logistics services (3PLP), has become more relevant than in previous years. Among the expectations of logistics service providers, and among the sources of competitive advantage, are timeliness and flexibility, which can only be handled and measured together, because of the integration of services. At the same time, when supply chains (not corporations) compete with each other, we must create the opportunity to manage chains beyond company boundaries. Our aim is to investigate the time-related problems of supply chains (and sections) and logistics service providers, and their consequences and solutions. We have found that the development of time factors which appear and can be measured in the realization of logistics services contributes to the competitiveness of a logistics service company. The performance provided by companies that are integrated into the supply chain’s member companies and operate as flexible logistics service providers can have a significant impact on the (full) operation and efficiency of the supply chain.